Humanness in Organisations : a Psychodynamic Contribution. - Vansina, Leopold (London : Karnac Books, 2013)
Humanness in Organizations is a unique contribution from the social sciences to the betterment of organizational life. The authors argue that working life can only become more humane when we change the conditions that consciously or unconsciously steer people away from consideration, friendship and integrity. The aim of this book is twofold: first, to take a closer look at the current practices of managers, academics, and consultants, and how they affect organizational conditions, work and the well-being of people. The critical studies presented here explore and develop the likely consequences.
CHAPTER SIX Processing mental representations of roles: alternating written and face-to-face interactionsCHAPTER SEVEN Facilitating transitional change; CHAPTER EIGHT Feedback or reviewing: a conceptual clarification of the differential impact on human beings and work systems; CHAPTER NINE Conversations on work; CHAPTER TEN Enacting one's way to new thinking: using critical incidents to vitalise authentic collaboration and learning; Epilogue; INDEX.
Print version record.
Keywords: Psychology; PSYCHOLOGY -- Reference; Psychology; Electronic books